Grain yield, net blotch and scald of barley in Finnish official variety trials - Robinson, Jonathan; Jalli, Marja (Agricultural and Food Science, 1997)
Data on grain yield, and terminal severity of net blotch (Pyrenophora teres f. teres) and scald (Rhynchosporium secalis) from Finnish official barley (Hordeum vulgare) variety trials were analysed to indicate the pattern of disease incidence over six years and five sites for nineteen barley genotypes, and the effect of the diseases on yield and the genotype by environment interaction for yield. The effect of climatic factors on net blotch severity were also investigated. The genotype by site interaction for net blotch severity was not statistically significant, but that for yield was. Net blotch severity differed between years, but was similar across sites and there were statistically significant first order interactions between year, site and genotype. ‘Saana’ and ‘Thule’ had relatively low mean terminal net blotch scores and their reaction to the disease was less sensitive to the environment than was that of ‘Tyra’ for example. Analysis of yield data adjusted for net blotch severity indicated that the magnitude of the genotype by environment interaction terms were not accounted for to any significant degree by differences in relative net blotch resistances among the barley genotypes. Overall, mean scores for scald severity were lower than those for net blotch. Terminal net blotch severity was correlated with May rainfall and growing degree days.